3 D Hierarchical Porous Carbon for Supercapacitors Prepared from Lignin through a Facile Template‐Free Method. Issue 12 (27th May 2015) - Zhang, Wenli; Lin, Haibo; Lin, Zheqi; Yin, Jian; Lu, Haiyan; Liu, Dechen; Zhao, Mingzhu
Abstract Lignin‐derived hierarchical porous carbon (LHPC) was prepared through a facile template‐free method. Solidification of the lignin–KOH solution resulted in KOH crystalizing within lignin. The crystalized KOH particles in solid lignin acted both as template and activating agent in the heat‐treatment process. The obtained LHPC, exhibiting a 3D network, consisted of macroporous cores, mesoporous channels, and micropores. The LHPC comprised 12.27 at % oxygen‐containing groups, which resulted in pseudocapacitance. The LHPC displayed a capacitance of 165.0 F g−1 in 1 M H2SO4 at 0.05 A g−1, and the capacitance was still 123.5 F g−1 even at 10 A g−1. The LHPC also displayed excellent cycling stability with capacitance retention of 97.3 % after 5000 galvanostatic charge–discharge cycles. On account of the facile preparation of LHPC, this paper offers a facile alternative method for the preparation of hierarchical porous carbon for electrochemical energy storage devices.